Foundations of non-cooperative game theory - Ritzberger, Klaus (Oxford ; New York : Oxford University Press, 2002)
This textbook brings together the main developments in non-cooperative game theory from the 1950s to the present. After opening with a number of lively examples, Ritzberger starts by considering the theory of decisions under uncertainty.
Includes bibliographical references (p. [331]-343) and indexes.
osc 18/03/14, opc 07/09/16
Loans
Keywords: Game theory; Non-cooperative games (Mathematics)